"Two-coil technique" for embolization of small internal carotid artery aneurysms incorporating the origin of the anterior choroidal artery. Issue 4 (August 2016) - Heo, Young Jin; Yang, Ku Hyun; Jung, Sung Chul; Park, Jung Cheol; Lee, Deok Hee
Purpose: The purpose of this article is to evaluate the efficacy, safety and stability of the "two-coil technique." Materials and methods: We evaluated a single-center experience by using a two-coil technique, which is a variation of the multiple-microcatheter technique in the treatment of a small internal carotid artery aneurysm with its sac incorporated with the origin of the anterior choroidal artery. Six consecutive patients with small ICA aneurysms with its sac incorporated with origin of the anterior choroidal artery and treated with the two-coil technique were included in this study. We finished the embolization with only two coils introduced via two different microcatheters without any other device assistance in all cases. Embolization status was determined at immediate postoperative and follow-up angiography after six months. Results: The two-coil technique was technically successful in five of six cases; one case was converted to surgical clipping because of persistent occlusion of the anterior choroidal artery after several attempts. On follow-up study, all five cases showed stable occlusion status without recanalization or residual aneurysm. Conclusions: The two-coil technique has potential to be used for coiling small aneurysms, particularly where there is an important branch incorporated into the sac or neck of the aneurysm.